Size‐Dependent Genetic Erosion due to Human Logging and Conservation Recommendation for an Endangered Yew (Taxus fuana) in Tibet, China - Xiao‐Lu Shen‐Tu; Yan Chen; Jun‐Yin Deng; Yao‐Bin Song; Ming Dong (Ecology and Evolution, 2025)
ABSTRACT Taxus fuana, an endemic plant of the West Himalayas, has an extremely small population size and is currently threatened by heavy logging due to its medicinal properties. However, the impacts of human‐induced logging on population size and tree size‐class distribution, and their consequences for genetic diversity in China remain unclear, constraining conservation efficacy. Field surveys across six Gyirong sites indicated that trees with basal diameters of 6–30 cm experienced the most severe logging damage, particularly at Jilong (JL) and Langjiu (LJ). Both chloroplast DNA (ɸST = 0.138) and nuclear SSR (FST = 0.091) revealed significant differentiation among sites. Demographic modeling and gene flow estimates suggest that restricted gene flow and enhanced genetic drift in smaller sites appear to have driven this differentiation. Moreover, genetic diversity declined in a size‐dependent manner: larger sites at Kaire (KR) and Jipu (JP) maintained higher haplotype diversity, nucleotide diversity, and allelic richness, whereas smaller sites at LJ and Tangbo (TB) exhibited markedly reduced values. At the individual tree level, sites dominated by small trees (6–30 cm) harbored lower genetic variation and allelic richness than those with a broader size‐class distribution, underscoring the link between logging‐induced demographic shifts and genetic erosion. We therefore recommend habitat restoration to prevent further logging, while establishing corridors and stepping‐stone sites to re‐establish gene flow and introducing genetically diverse individuals into sites with a high proportion of small trees.